Factors of Consumer Behavior That Affect Purchasing Decisions on Blackberry Smartphone - Nawawi, Muhammad Tony (Journal the Winners: Economics, Business, Management, and Information System Journal, 2016)
This study aimed to determine factors of consumer behavior that affect to purchasing decision on BlackBerry Smartphone with the case study in Faculty of Economics, Tarumanagara University, Jakarta. The population was all students of faculty of economics who used or were familiar with the BlackBerry brand mobile phone, with a sampling technique used was purposive random sampling and samples were taken by 200 students. The purpose of the study was to examine and analyze some factors that affect students in the decision to buy BlackBerry mobile phone brands and know the dominant factors that influence the purchase decision. Theanalysis used the method of multiple regression analysis and hypothesis testing and also testing conducted validity and reliability by using the help of SPSS (Statistical Program for the Science Society). The analysis shows that there is significant positive effect between the factors of cultural, social, personal, and psychological effect on purchasing decisions, with significance 0,000 < 0,05, and Adjusted R Square is worth 0,216, it means that 21,6% of purchase decisions are influenced by these factors.